Evidence of a shallow persistent magmatic reservoir from joint inversion of gravity and ground deformation data: The 25–26 October 2013 Etna lava fountaining event. Issue 7 (14th April 2016) - Greco, Filippo; Currenti, Gilda; Palano, Mimmo; Pepe, Antonio; Pepe, Susi
Abstract: To evaluate the volcanic processes leading to the 25–26 October 2013 lava fountain at Mount Etna, we jointly investigated gravity, GPS, and DInSAR measurements covering the late‐June to early‐November time interval. We used finite element modeling to infer a shallow magmatic reservoir which (i) inflated since July 2013, (ii) fed the volcanic activity at the summit craters during 25–26 October, and (iii) deflated due to magma drainage related to this volcanic activity. We suggested that this reservoir belongs to a shallow volume, which is located beneath the summit area and is replenished by magma rising from deep reservoirs and fed the short‐term volcanic activity, representing a persistent shallow magmatic plumbing system of Etna. In addition, the model results show that there is a large discrepancy between the erupted and shallow reservoir deflation volumes, which could be reasonably attributable to a highly compressible volatile‐rich magma. Key Points: Gravity and deformation signatures of the 26 October 2013 Mount Etna lava fountain Integrated finite element‐based inversion of gravity and GPS data Inference on a highly compressible volatile‐rich magma in the magmatic reservoir